Consensus-based recommendations for the management of juvenile localised scleroderma - Zulian, Francesco; Culpo, Roberta; Sperotto, Francesca; Anton, Jordi; Avcin, Tadej; Baildam, Eileen M; Boros, Christina; Chaitow, Jeffrey; Constantin, Tamàs; Kasapcopur, Ozgur; Knupp Feitosa De Oliveira, Sheila; Pilkington, Clarissa A; et al. (Elsevier, 2019)
In 2012, a European initiative called Single Hub and Access point for paediatric Rheumatology in Europe (SHARE) was launched to optimise and disseminate diagnostic and management regimens in Europe for children and young adults with rheumatic diseases. Juvenile localised scleroderma (JLS) is a rare disease within the group of paediatric rheumatic diseases (PRD) and can lead to significant morbidity. Evidence-based guidelines are sparse and management is mostly based on physicians' experience. This study aims to provide recommendations for assessment and treatment of JLS. Recommendations were developed by an evidence-informed consensus process using the European League Against Rheumatism standard operating procedures. A committee was formed, mainly from Europe, and consisted of 15 experienced paediatric rheumatologists and two young fellows. Recommendations derived from a validated systematic literature review were evaluated by an online survey and subsequently discussed at two consensus meetings using a nominal group technique. Recommendations were accepted if ≥80% agreement was reached. In total, 1 overarching principle, 10 recommendations on assessment and 6 recommendations on therapy were accepted with ≥80% agreement among experts. Topics covered include assessment of skin and extracutaneous involvement and suggested treatment pathways. The SHARE initiative aims to identify best practices for treatment of patients suffering from PRDs. Within this remit, recommendations for the assessment and treatment of JLS have been formulated by an evidence-informed consensus process to produce a standard of care for patients with JLS throughout Europe.
Keywords: DMARDs (biologic); methotrexate; systemic sclerosis